A case-control study to determine the risk factors of dengue fever in Chattogram, Bangladesh - Md Sahidur Rahman; Fatema Mehejabin; Mohammad Arafat Rahman; Rumana Rashid (Elsevier, 2022)
Objectives: In a tropical country like Bangladesh, where the climatic condition favors the growth of Aedes mosquito vectors, the success of dengue prevention depends largely on the proper identification and control of risk factors. Therefore this study was aimed to explore the potential risk factors and their association with dengue infection. Study design: A case-control study including 150 cases and 150 controls was conducted in Chattogram district of Bangladesh. Cases were confirmed dengue patients admitted in Chattogram medical college hospital and Bangladesh institute of tropical and infectious diseases during August and September 2019. On the other hand, controls were non-dengue patients admitted in other departments of the same hospitals through gender, age, and location matching. Methods: The questionnaire data were collected through telephone-based interviews, which included general demography, daily life activities, housing and surrounding environment of participants. Chi-square and binary logistic regression were performed to identify potential risk factors. Results: The study found that travel history to the high incidence area, staying most of the daytime in office (AOR = 18.10), living in 21-40 years old houses (AOR = 9.74), and the temporary residency in the city (AOR = 10.20) were statistically significant risk factors for getting dengue infection. However, day time sleep, house type and structure, number of family members, morning and evening walk, plant in resident, and junk yard around 250 m of the house were also showed a significant effect in chi square test. Conclusions: Results strengthen our understanding regarding the role of factors associated with daily lifestyle and living environment of people in the development of dengue and hence support the dengue control program in Bangladesh. The study will provide a basis for future extended research covering different parts of the country.